(untitled) (Sociologisk Forskning, 2023)
Almost three decades have passed since the publishing of the last, and only, special issue on the sociology-environmental nexus in this journal. Since then, few of the articles published in Sociologisk Forskning have addressed climate change at all or in any substantial way. This silence could be interpreted as a quiet statement that sociology does not need to concern itself with climate change. However, no such line of argument is suggested in this special issue “Climate crisis”, which (re)presents current Swedish sociological research on climate change. Many of the authors take a similar stance that (environmental) sociology should not shy away from the climate crisis and the societal project of transformative change. Rather, sociologic research should study empirical cases of climate transitions or transformations, and contribute suggestions, as well as explanations, to how such changes can be accelerated.